2023
DOI: 10.1007/s11064-023-03964-2
|View full text |Cite
|
Sign up to set email alerts
|

G6PDi-1 is a Potent Inhibitor of G6PDH and of Pentose Phosphate pathway-dependent Metabolic Processes in Cultured Primary Astrocytes

Abstract: Glucose-6-phosphate dehydrogenase (G6PDH) catalyses the rate limiting first step of the oxidative part of the pentose phosphate pathway (PPP), which has a crucial function in providing NADPH for antioxidative defence and reductive biosyntheses. To explore the potential of the new G6PDH inhibitor G6PDi-1 to affect astrocytic metabolism, we investigated the consequences of an application of G6PDi-1 to cultured primary rat astrocytes. G6PDi-1 efficiently inhibited G6PDH activity in lysates of astrocyte cultures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…An additional pathway that may contribute to the disappearance of 2DG6P from cultured astrocytes is the oxidation In panel (c), the significance of differences (t-test) between the data obtained for incubations in the absence and the presence of 2DG is indicated by # p < 0.05 and ## p < 0.01 of 2DG6P by G6PDH, as 6-phospho-2-deoxygluconate has been found in the brain of 2DG-exposed rats [4]. We have previously shown that cellular NADPH regeneration via the PPP can be studied by monitoring the NQO1-dependent reduction of extracellular WST1 to its formazan in the presence of the redox cycler β-lapachone [26,42]. In the presence of 2DG the glucose-independent WST1 reduction was almost doubled in a concentration-dependent manner by 2DG, suggesting that 2DG6P acts as substrate of G6PDH in living astrocytes, thereby providing electrons via NADPH for the WST1 reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional pathway that may contribute to the disappearance of 2DG6P from cultured astrocytes is the oxidation In panel (c), the significance of differences (t-test) between the data obtained for incubations in the absence and the presence of 2DG is indicated by # p < 0.05 and ## p < 0.01 of 2DG6P by G6PDH, as 6-phospho-2-deoxygluconate has been found in the brain of 2DG-exposed rats [4]. We have previously shown that cellular NADPH regeneration via the PPP can be studied by monitoring the NQO1-dependent reduction of extracellular WST1 to its formazan in the presence of the redox cycler β-lapachone [26,42]. In the presence of 2DG the glucose-independent WST1 reduction was almost doubled in a concentration-dependent manner by 2DG, suggesting that 2DG6P acts as substrate of G6PDH in living astrocytes, thereby providing electrons via NADPH for the WST1 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The WST1 reduction method that we have used to investigate the potential of accumulated 2DG6P to serve as substrate for the PPP or to inhibit the use of G6P by G6PDH is based on the NADPH-dependent reduction by NQO1 of the electron cycler β-lapachone that subsequently permeates in reduced form the cell membrane and reduces extracellular WST1 [26,42,48]. This indirect method allows conclusions on the electron flow through the PPP but gives no information on the cellular level of NADPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from a study on cultured astrocytes demonstrated that G6PDi−1 (10 µM) inhibited 60% of the supply of electrons for a NQO1-catalysed β-lapachone-mediated reduction in the water-soluble tetrazolium salt 1, suggesting that NADPH, derived from PPP, is the main source of electrons for cytosolic NAD(P)H quinone oxidoreductase 1 (NQO1) [43]. Importantly, another study from this group provided compelling evidence that G6PDi−1 efficiently and specifically inhibits astrocytic G6PDH without affecting other oxidoreductases, indicating that G6PDi−1 is a suitable and specific tool for inhibiting G6PDH and PPP-dependent processes [44].…”
Section: Effect Of G6pdi−1 On Glucose Consumption Induced By Shaffer ...mentioning
confidence: 99%
“…Previous research on cultured astrocytes has shown that NADPH produced in the PPP is involved in several NADPH-dependent intracellular reactions, such as the function of cytosolic NAD(P)H-quinone oxidoreductase 1 (NQO1) [44].…”
Section: Effect G6pdi−1 On On Nad(p)h/nad(p) Levelsmentioning
confidence: 99%